Dividend Taxes and Share Prices: Evidence from Real Estate Investment Trusts - Getry, William M.; Kemsley, Deen; Mayer, Christopher J. (Journal of Finance, 2003)
Prior empirical evidence regarding the impact of dividend taxes on firm valuation is mixed. This study avoids some of the complications encountered in previous empirical work by exploiting institutional characteristics of REITs, such as their limited discretion over dividend policy and the relative transparency of REIT assets. We regress the market value of equity on the market value of assets and tax basis, which creates tax deductions that lower future dividend taxes without affecting future pretax cash flow. We find that firm value is positively related to tax basis, suggesting that future dividend taxes are capitalized into share prices.